2010
DOI: 10.1021/nn1014769
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Surface Modified Virus Capsids for Targeted Delivery of Photodynamic Agents to Cancer Cells

Abstract: Bacteriophage MS2 was used to construct a targeted, multivalent photodynamic therapy vehicle for the treatment of Jurkat leukemia T cells. The self-assembling spherical virus capsid was modified on the interior surface with up to 180 porphyrins capable of generating cytotoxic singlet oxygen upon illumination. The exterior of the capsid was modified with ∼20 copies of a Jurkat-specific aptamer using an oxidative coupling reaction targeting an unnatural amino acid. The capsids were able to target and selectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
199
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(202 citation statements)
references
References 67 publications
2
199
0
1
Order By: Relevance
“…Indeed, iodoacetamide is used routinely for capping before digestion for protein sequencing 17 . Notably, some derivatives react with N-nucleophiles 18 . However, commercial availability and ease of use and synthesis of maleimide derivatives 13,19 have led to widespread use (for example, vaccine candidates 20 or modified enzymes 21 ) 13 .…”
Section: Modifications Of Natural Amino Acidsmentioning
confidence: 99%
“…Indeed, iodoacetamide is used routinely for capping before digestion for protein sequencing 17 . Notably, some derivatives react with N-nucleophiles 18 . However, commercial availability and ease of use and synthesis of maleimide derivatives 13,19 have led to widespread use (for example, vaccine candidates 20 or modified enzymes 21 ) 13 .…”
Section: Modifications Of Natural Amino Acidsmentioning
confidence: 99%
“…However, rational modification to the exterior of VLNPs aims to use the strength of polyvalent interactions to engineer novel specificity for cell surface receptors. To this end, VLNPs have been functionalized with diverse ligands to tumor-associated targets such as peptides [7], antibodies [8], other proteins such as EGF [9], as well as glycans [10], aptamers [11] and small molecules such as folic acid [12]. These studies and others have shown remarkably efficient and specific in vitro targeting.…”
Section: Cancer Cell Targetingmentioning
confidence: 99%
“…A range of MRI and positron emission tomography agents have also been delivered by VLNPs [17]. Finally, VLNPs have been used to encapsidate high payloads of small molecule therapeutics such as doxorubicin [14], as well as photodynamic agents for light-triggered reactive oxygen generation [10,11].…”
Section: Cancer Cell Targetingmentioning
confidence: 99%
“…For example, VLPs have been targeted to specific cells including melanoma cells and lymphocytes by attaching antibodies and peptides to their outer surface [20]. They have also been used for the delivery of chemotherapeutic agents such as the anticancer drug doxorubicin [15] and photodynamic agents like singlet oxygen [21], both of which were encapsulated inside the protein cage.…”
Section: Nanobubble Preparation and Imagingmentioning
confidence: 99%
“…Protein cage structures such as those mentioned above have been studied for their potential in materials synthesis [7,12], catalysis [13,14], drug and gene delivery [15,16], bio-imaging [17][18][19], cell targeting [20,21], and vaccine development [11]. VLPs in particular are promising, as they exist in a large range of sizes (tens to hundreds of nanometers), have well-defined, monodisperse structures, can be purified in large quantities, and can be easily modified both genetically and chemically [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%